DMD 빔 투과 광학계 개선을 위한 서브 마이크론급 압전 정렬 기술 개발 - 홍민성(Min Sung Hong); 이형규(Hyung Ku Lee); 박종서(Jong Seo Park) (한국생산제조학회지, 2017)
Except for the exposure optical system (optical imaging system + light irradiation optical system), the other field technology has secured the base and some core technologies, but it has a high precision positioning alignment technique of the optical imaging optical system that directly affects the result of fine pattern processing of actual products. There is an urgent need to secure. We have studied the alignment method of aperture array of optical imaging system using piezo element. We developed a jig that can align an aperture array using a piezo actuator, and the exposure results were confirmed by aligning the aperture array with the developed imaging optical system. The conclusion is that the alignment method of the aperture array of the optical imaging system using the piezo element led to good results. KCI Citation Count: 0